CLAPS: Course and Lecture Assignment Problem Solver for Educational Institution Using Hungarian Method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A linear programming relates to solve the complicated problem concerning distribution of various resources such as men, machine, money, material, and time quantity satisfying certain constraints in the form of algebraically represented linear equations/inequalities.so as to maximize the profit or minimize the cost. The Assignment Technique is applied in the class of very practical linear programming model to assign a number of source variable jobs or persons to equal number of machines or tasks with minimum cost or maximum profit. The job to machine or person to task selection complicacy is generally known as Assignment problems. In this paper the Assignment problem objective is to assign a number of sources (jobs) to equal number of faculties (persons) at a minimum cost to manage the listed courses in an educational institution’s various lecturer arrangements. Assignment problem arises while n number of jobs are assigned to m number of machines, where  may or may not equal to  and the number of persons is intended to operate m number of machines or engage n number of cranes at m number of quarries. The assignment, employment or allotment is targeted with the goal to expend minimum cost or maximum effectiveness in the operation. The assignment problems are usually solved by using Hungarian method. In case, more restrictions or constraints are imposed in the jobs dimension or machines tool instruments’ performance, or energy consumptions restrictions the assignment goal simplicity hampers and out of track. So, in spite of computational logistic flow diagrams availability, there is inadequate computer programming methods available to implement Hungarian method to solve the assignment problem. In this paper, the authors presenting the Hungarian method applied case study that discusses the Course and Lecturer assignment problem solvation process adopted by a course coordinator in tertiary institution (CLAPS). Despite the usefulness of operations research techniques in both manufacturing and service sectors, course coordinators in the regional institutions still make use of heuristic approach while assign courses to lecturers in department which rarely bring out maximum effectiveness in these lecturers. The study demonstrates the usefulness of Hungarian method in solving course assignment problem in a specific institution. The assignment problem was formulated and solved with Hungarian method based on the data obtained from five lecturers in a department in the specific department in the specific institution. So, it is necessary for the administrators to use Operation Research techniques are as powerful tools in decision making.